The Prairie: Its Season and Rhythms - Louis Copt (Symphony in the Flint Hills, 2012)
Art work and a quote from Louis Copt on the seasons of Kansas.
Keywords: poem; story; song; Flint Hills; summer; Louis Copt; Konza Prairie Sunset; Hidden Pond; Snowy Path; seasons; Adrift